LMP-associated proteolytic activities and TAP-dependent peptide transport for class 1 MHC molecules are suppressed in cell lines transformed by the highly oncogenic adenovirus 12 - Rotem-Yehudar, Rinat; Groettrup, Marcus; Soza, Andrea; Kloetzel, Peter-Michael; Ehrlich, Rachel (My University, 1996)
Expression of class I major histocompatibility complex antigens on the surface of cells transformed by adenovirus 12 (Ad12) is generally very low, and correlates with the in vivo oncogenicity of this virus. In primary embryonal fibroblasts (H-2b) that express transgenic swine class I antigen (PD1), Ad12-mediated transformation results in inhibition in transport of newly synthesized class I molecules, as well as significant reduction in transporter associated with antigen presentation (TAP) gene expression. In this report we show that reexpression of TAP molecules either by stable transfection of mouse TAP genes or by infection with recombinant vaccinia viruses expressing human TAP genes, only partially reconstitutes the expression and transport of the class I molecules. Further analysis of Ad12-transformed cells revealed that the expression of both LMP2 and LMP7, but not of other proteasome complex components, was downregulated, resulting in altered proteolytic activities of the 20S proteasomes. Reconstitution of both TAP and LMP expression resulted in complete restoration of PD1 cell surface expression and enhanced expression of the endogenous H-2D(b) molecules encoded by recombinant vaccinia viruses, in reconstituted Ad12-transformed cells, efficient transport of H-2 class I molecules could only be achieved by treatment of the cells with gamma-interferon. These data suggest that an additional factor(s) that is interferon-regulated plays a role in the biosynthetic pathway of the class I complex, and that its function is deficient in this cell system. Thus, Ad12 viral transformation appears to suppress the expression of multiple genes that are important for antigen processing and presentation, which allows such transformed cells to escape immune surveillance. This coordinate downregulation of immune response genes must likely occur through their use of common regulatory elements.
Keywords: 570